Comparison of intravitreal bevacizumab to photodynamic therapy for polypoidal choroidal vasculopathy: Short-term results - Mitamura, Yoshinori (Medknow Publications, 2010)
AIMS: To compare the short-term therapeutic effects of intravitreal bevacizumab (IVB) to those of photodynamic therapy (PDT) for polypoidal choroidal vasculopathy (PCV). MATERIALS AND METHODS: Retrospective interventional case study. Eighty-nine eyes of 89 patients with symptomatic PCV were treated by IVB or PDT. Eighteen eyes were treated with a single injection of IVB (s-IVB group), 22 eyes with three consecutive monthly IVB injections (m-IVB group), and 49 eyes with PDT alone (PDT group). The best-corrected visual acuity (BCVA) and OCT-determined central foveal thickness (CFT) were evaluated before, and one and three months after the treatment. For statistical analyses, one-factor ANOVA and Chi-square test were used. RESULTS: The differences in the BCVA and CFT among the three groups at the baseline were not significant (P=0.992, P=0.981, respectively). Three months after the treatment, the BCVA improved by >0.2 logMAR units in two out of 18 eyes (11%) in the s-IVB group, three out of 22 eyes (14%) in the m-IVB group, and 15 out of 49 eyes (31%) in the PDT group (P=0.124). A decrease in the CFT by >20% was achieved in six out of 18 eyes in the s-IVB group, ten eyes (46%) in the m-IVB group, and 35 eyes (71%) in the PDT group (P=0.009). The resolution of polyps was achieved in three out of 18 eyes in the s-IVB group, one eye (5%) in the m-IVB group and 35 eyes (71%) in the PDT group (P<0.001). CONCLUSION: The better short-term therapeutic outcomes in the PDT group than in the s-IVB and m-IVB groups indicate that PDT may be more effective than IVB in short term after treatment for PCV.